(untitled) (Discourse of Law and Administration, 2026)
This paper examines the principle of complementarity in the context of recent legislative reforms governing access to the Polish labour market for foreign nationals. The analysis focuses on the period preceding and following the adoption of the Act on the conditions of admissibility of the employment of foreigners in the territory of the Republic of Poland, highlighting the normative evolution of regulatory instruments. Drawing on a comparative legal perspective, the study explores whether the changes introduced constitute a reaffirmation of the existing regulatory approach or mark a departure therefrom – amounting to a mirror reversal of the previously applicable framework. Special attention is given to the shift from automatic, mandatory restrictions such as the labour market test to discretionary mechanisms whose activation depends on the intervention of public authorities. By identifying structural continuities and discontinuities in the application of the complementarity principle, the paper contributes to a broader understanding of the current direction of Poland’s migration and labour market policy, as well as the underlying assumptions guiding the employment of third-country nationals.